Pengembangan E- Modul Emolien Berbasis Adobe Flash CS6 pada Materi SPLDV - Agatha Nuraini, Fika Widya Pratama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is a research and development (R&D) to develop a learning media as an e-module accessible via smartphones. It contains SPLDV materials for grade VIII students at Stella Matutina Junior High School. The purpose is to assess the feasibility, effectiveness, and practicality of the EMOLIEN e-module. SPLDV is a fundamental subject at the junior high school level, and students often face difficulties in answering SPLDV questions. The EMOLIEN e-module was developed using Adobe Flash CS6 software, following the ADDIE development model, which comprises the analysis, Design, Development, Implementation, and Evaluation phases. This research was implemented on March 4, 2024, in the even semester of the 2023/2024 school year at Stella Matutina Junior High School. Data was collected through media and material validation sheets, student response questionnaires, teacher response questionnaires, as well as pretest and posttest. The study results demonstrate that the EMOLIEN e-module was developed according to the ADDIE procedure and obtained a validity test of EMOLIEN learning media, with 91% of material experts and 98% of media experts indicating very feasible (valid) results. The results of the student response questionnaire were 82%, while the teacher response questionnaire was 82%, indicating a high level of practice. The effectiveness results were evidenced by the increase in the average pretest score on the posttest score from 30.5 to 52.25 and strengthened by the Asymp results. Sig. (2-tailed) < 0.05, indicating effectiveness. In conclusion, this EMOLIEN e-module meets the criteria of validity, practicality, and effectiveness.